A Study of 219Rn Outgassing and 211Pb Contamination from 223Ra In dry, Liquid, and Murine Tissue Samples. Issue 2 (February 2020) - Adler, Stephen; Baidoo, Kwamena; Jagoda, Elaine; Phelps, Tim; Roy, Jyoti; Seidel, Jurgen; Lin, Frank; Choyke, Peter
Abstract : Abstract: Introduction: A study of 211 Pb contamination caused by the outgassing of 219 Rn from 223 Ra in dry, liquid, and murine tissues samples has been made to help design proper handling procedures for 223 Ra in preclinical biodistribution work. Materials and Methods: 211 Pb activity levels were measured from 223 Ra in dry, liquid, and tissue samples using aspiration and autoradiography techniques. Results: Using aspiration techniques on dry samples of 223 Ra, an average 219 Rn outgassing rate of 51% ± 21% was measured with one measurement reaching as high as 81%. 31% ± 4% 211 Pb contamination was measured within a 4.3 cm radius of a dry 223 Ra source placed inside a 10-cm-diameter petri dish where the lip of the petri dish contained the 219 Rn dissemination. Without the containment of the petri dish, 219 Rn can reach as far as 7.8 cm from the source with trace levels spreading further. Using aspiration techniques on liquid samples of 223 Ra, outgassing rates of 219 Rn were 0.9% ± 0.3%. The outgassing levels in harvested organs from a biodistribution were as high as 10.1% ± 0.4% for an intraperitoneally injected mouse and 0.204% ± 0.006% for an intravenously injected mouse. The outgassing of the intravenously injected mouse carcass was less than 0.1%. Conclusion: In dry form, the high levels of 219 Rn outgassing from a 223 Ra source necessitate the use of ventilated biohoods when handling or preparing dry 223 Ra from source vials. The very low levels of 219 Rn outgassing from 223 Ra liquid sources reduces exposure to 219 Rn by a factor of 50. 219 Rn exposure from murine organ tissue reaches levels of 10% when handling organs from an intraperitoneal injection and less than 0.2% for an intravenous injection.